THE INFLUENCE OF WORD GROUPING ACTIVITIES TOWARDS STUDENTS’ VOCABULARY MASTERY AT THE FIFTH CLASS OF SD NEGERI I BAGELEN GEDONGTATAAN PESAWARAN - Alfiawati, Riska (Lentera: Jurnal Ilmiah Kependidikan, 2016)
Vocabulary is one of the key elements for understanding an entire subject. When the language is learn, students see what they have not seen before. So, they can communicate in ways that are unique from one subject to the next. A large vocabulary opens students up to a wider range of reading materials. Rich vocabularies also improve students’ ability to communicate through speaking, listening and writing. In learning vocabulary, the teachers should give the chance to use vocabularies in the activity such as on the game, and the important thing, it should be appropriate with the curriculum and take the students’ motivation on the lesson. The writer used total sampling technique in taking the sample. For the data collecting technique, the writer used objective test to get the students’ vocabulary mastery, which is multiplechoice test consisting of 40 items with 4 options. In data analysis the writer used ttest formula. This research showed that the average score of students’ vocabulary mastery who learn vocabulary through Word Grouping Activities was higher than those students who learn vocabulary through the conventional technique ( 1 X = 66.26 > 2 X =56.32). Then, the result of data calculation, ttest was higher than ttable (3.12>2.39). Therefore, the writer concluded that Word Grouping Activities gave positife influence towards students’ vocabulary mastery at the fifth class of SD Negeri I Bagelen Gedongtataan Pesawaran in 2015/2016.